Plate XII: Ascidia and amphioxus - Haeckel, Ernst (Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, 1872)
Plate depicts the development of ascidia (figure A) and amphioxus (figure B). Ascidia are also known as ascidians or sea squirts and are marine invertebrate filter feeders. Amphioxus, also known as lancelet, are small marine animals that are members of invertebrate subphylum Cephalochordata of the phylum Chordata. This plate can be found in Ernst Haeckel's Natürliche Schöpfungsgeschichte: Gemeinverständliche Wissenschaftliche Vorträge über die Entwickelungslehre, or The History of Creation: Or the Development of the Earth and Its Inhabitants by the Action of Natural Causes.
Keywords: Evolution; Heredity; Amphioxus; Sea squirts; Marine invertebrates